Prognostic relevance of sunitinib toxicities and comparison of continuous vs. intermittent sunitinib dosing schedule in metastatic renal cell cancer patients - Çetin Ordu; Kezban N. Pilanci; Nilüfer Avcı; İbrahim Yıldız; Gül Alço; Özkan Demirhan; Ülkühan I. Köksal; Filiz Elbüken; Coskun Tecimer; Gökhan Demir (Contemporary Oncology, 2016)
Aim of the study : Sunitinib-related side effects may develop as a result of the pharmacokinetic pathway affects the of the drug. Material and methods : Data on mRCC patients were obtained from the hospital archives. Outcomes of patients were evaluated in terms of related prognostic factors, sunitinib adverse events during the treatment, and two different sunitinib dosing schedules. Results : Seventy patients diagnosed with mRCC and treated with sunitinib were analyzed for prognostic factors and survival rates. During the mean follow-up of 33.5 months, 38 (54%) patients were alive and 32 (46%) patients died. The median time of overall survival (OS) and progression-free survival (PFS) was 27 months (12–61) and 19 months (5–45), respectively. In univariate analysis, good prognostic risk group according to the Memorial Sloan-Kettering Cancer Center (MSKCC), hypothyroidism as sunitinib toxicity and patients on sunitinib treatment more than 1 year were favorable prognostic factors for OS. Leukopenia and fatigue as sunitinib toxicity were poor prognostic factors for OS. PFS and OS of the patients were not significantly different when we compared intermittent (4/2) vs. continuous treatment dosing schedules. Conclusions : As a result of this trial, having hypothyroidism as an adverse effect of sunitinib was a favorable prognostic factor for OS and PFS in mRCC patients. It was also found that 4/2 and continuous dosing schedules of sunitinib did not give rise to different outcomes in mRCC patients.